Making an Effective Virtual Scientific Poster Presentation - Joe Barrett Carter; Jithran Ekanayake; Taisha Venort; Kelsey Vought; Shannon Noble; Adam Watson (EDIS)
This publication aims to provide guidance, strategies, and recommended tools to help aspiring presenters effectively adapt to the virtual environment and present their findings. Written by Joe Barrett Carter III, Jithran Ekanayake, Taisha Venort, Kelsey Vought, Shannon Noble, and Adam Watson, and published by the UF/IFAS Department of Agricultural and Biological Engineering, December 2023.